Vídeos unboxing e publicidade infantil: a responsabilidade civil do youtuber anunciante - Santos, Bruna Aline Freire dos (Universidade Federal do Tocantins, 2021)
The digital platform YouTube has become popular among children and a practice whose popularity is increasing on that space is the unboxing, which consists of videos where the protagonists, called YouTubers, present the opening and demonstration of new products, such as toys and collectible items. This paper aimed to analyze, under the Consumer Law, if the possible advertisement served in these videos creates civil liability for illicit advertising of the advertiser YouTuber. For that, exploratory research of bibliographic, in academic publications, and documentary nature, in the decisions of the Brazilian Advertising Self Regulation Council, was carried out. The inductive method was used, since it started from an analysis of specific facts about the performance of the YouTubers to a general conclusion about the civil liability for illicit advertising. The presence of elements of illicit advertising was verified in the unboxing videos, not only because of the unconscionability of targeting children, but also due to the veiled character of the advertisement. Moreover, results showed that YouTubers that share such contente have objective civil liability, because they actively participate in the elaboration of the advertisement and may receive consideration from the supplier, in addition to having great influence on their followers.